Clinical Application of Adaptive Immune Therapy in MSS Colorectal Cancer Patients - Wang, Danyang; Zhang, Hangyu; Xiang, Tao; Wang, Gang (Frontiers in Immunology, 2021)
Colorectal cancer (CRC) is one of the most common cancers worldwide. However, the treatment outcomes of immunotherapy in microsatellite-stable (MSS) CRC remain unsatisfactory. As the majority of CRC cases display a molecular MSS/mismatch repair-proficient (pMMR) profile, it is particularly meaningful to explore the clinical applications of adaptive immune therapy in MSS CRC patients. In this review, we summarized the therapeutic approaches of adoptive immune therapies, including cytokines, therapeutic cancer vaccines, adoptive T-cell therapy, and immune checkpoint inhibitors, in the treatment of MSS CRCs.